Analisis Penyajian PSAK 65 dan Relevansinya Terhadap PSAK 22 Dan PSAK 15 pada Laporan Keuangan Konsolidasi Perusahaan PT Mulia Industrindo Tbk. (Jurnal Kendali Akuntansi, 2024)
The presentation of Consolidated Financial Statements is regulated by the guidelines contained in the Statement of Financial Accounting Standards (PSAK) 65. Apart from these regulations, there are two additional PSAKs which regulate relevant aspects related to the presentation of Consolidated Financial Statements, namely PSAK 22 concerning Accounting for Business Combinations and PSAK 15 concerning Accounting for Investments in Associated Companies. This study aims to analyze the presentation of the Statement of Financial Accounting Standards (PSAK) 65 and its relevance to PSAK 22 and PSAK 15 in the context of preparing the Consolidated Financial Statements of PT Mulia Industrindo Tbk. The research method used is literature review with reference to on exploring published literature sources, especially articles has been published in a scientific journal. The research results show that PT Mulia Industrindo Tbk. hasimplementing PSAK 65 and being relevant to PSAK 22 and PSAK 15 in its consolidated financial statements is proven apply the ownership consolidation method in using its financial statements, which indirectly reflect activities business combination.